WOMEN IN SCIENCE: THE SCIENTISTS OF PERNAMBUCANAS ACADEMIES - da Conceição, Josefa Martins; Pereira, Juliana Carvalho; Teixeira, Maria do Rocio Fontoura (Cadernos de Educação Tecnologia e Sociedade, 2019)
This article aims to identify the scientists of the Pernambuco Academy of Agronomic Science, the Pernambuco Academy of Veterinary Medicine and the Pernambuco Academy of Chemistry, highlighting their professional trajectories, contributions in the production of knowledge and their relevance to the history of science in Pernambuco. As a methodological procedure, it was used the analysis of the documentary records of the scientists in the collection of each Academy, based on the primary sources, the official documents: statutes and regiments, printed and electronic records and biographical profile. Complementing this information is the analysis of Lattes Curricula. In addition to contextualizing and rescuing the Pernambuco pioneers, this study reveals that in the 1940s, women were admitted to the then male centers of Agronomy, Chemistry and Medicine and, in the 1950s, in Veterinary Medicine. The female participation in these courses has gradually increased and, nowadays, has as a differential the growing number of students. It is evident that, in the gender relation, male participation occupies the largest number in these Academies. In them, the actions of these women in the conquest of the feminine space in science in Pernambuco are visible.